Spectrographic Analysis of Dysarthric Speech - Rajkumar Pandita (Journal of All India Institute of Speech and Hearing, 1970)
"Speech basically  results  by  three motor processes ; exhalation, phona- tion and articulation. For each speech sound there is a separate neuromuscular configuration that  involves as a functional  unit,  all the  musculature of  the speech  organ" (West and Ansberry, 1968).